PENGARUH PENAMBAHAN BERBAGAI KONSENTRASI Na-CMC TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK ES KRIM SARI BIJI NANGKA - Sudajana, Fanny Laurensia; Utomo, Adrianus Rulianto; Kusumawati, Netty (Widya Mandala Surabaya Catholic University, 2013)
Jackfruit seeds can be processed to a powder, starch, or extracted. Jackfruit seeds extract is simply processed from jackfruit seeds, its stages are shelling beans, boiling, extraction, and filtration. The utilization of jackfruit seeds extract in ice cream making is still unknown about how precisely the concentration of Na-CMC so it will produce a good quality of jackfruit seed extract ice cream. This is because there are some components in jackfruit seed extract that can bind water like starch and soluble fibers so hopefully the addition of Na-CMC can be reduced. In this study, a Randomized Blocked Design is used. A concentration Na-CMC (0.5%, 0.75%, 1%, 1.25%, 1.5%), used as a factor and each treatment was repeated five times. Testing parameters includes the physicochemical properties (viscosity, overrun, total solids and the rate of melting) and organoleptic (test preference for softness of the ice crystals and rate of melting in the mouth). Furthermore, the data obtained were analyzed statistically using ANOVA test (Analysis of Variance) at = 5% and DMRT (Duncan's Multiple Range Test) with = 5%. Weighting test is also performed to determine which treatment is the best. The addition of various concentrations of Na-CMC gave a significantly different effect on the viscosity, overrun, total solids, the rate of melting, and organoleptic. The higher the concentration of Na-CMC viscosity, overrun, total solids increased, and the lower the rate of melting. Ice cream with jackfruit seed extract concentration of 1.25% Na-CMC most preferred to the softness of the ice crystals in the mouth, while the seeds of jackfruit ice cream sari with Na-CMC concentration of 0.75% preferred to melting in the mouth. Based on the weighting test, treatment of jackfruit seed ice cream sari with the addition of 1.25% Na-CMC is the best treatment.